Food policy and food security in Northern Bangladesh: An empirical study of the impact of food policy on household food security - Naznin Sultana; Gabriela Sabau (Social Sciences and Humanities Open, 2023)
Food insecurity is an ongoing national concern both in developing and in developed countries. Well-designed food policies, including aspects such as food production, distribution, consumption, availability, purchasing procedures, techniques of food processing and marketing, and food support, may contribute to solving the problem of food insecurity at household level. We study the impact of government provided food support on the households’ daily calorie intake, as well as on the food security index by using survey data from three sub-districts (Puthia, Paba and Charghat) of the Rajshahi district in Bangladesh. The survey was conducted using 160 households out of which 41.9 percent were food support receivers and 58.1 percent were food support non-receivers. The extent of food insecurity among the respondents was estimated by calculating the daily mean calorie intake and the food security index. The PSM (propensity score matching) technique was used to assess the effects of government food support on rural households’ food insecurity. The results have shown that dissimilarities exist in unobserved characteristics between the two groups, as food prices and own agricultural production may influence the households’ decision to receive or not government food support. This has influenced the calorie intake and the food security index of the sample respondents. A comparison of the means of the matched sample showed that the two groups did not differ in food expenditure. Therefore, the impact of government food support on the calorie intake or the food security index may not be underestimated. The study concluded that food policy in the form of government food support can be efficiently implemented in a well-functioning socio-economic system.